The Livelihood Strategy of Rubber Tapper Households - Elia Patar Karunia Silaban; Sriroso Satmoko; Kadhung Prayoga (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2021)
Livelihood strategy is a method or tactic that used by a person or group to survive by using assets condition that they have, such as human capital, physical, nature resource, financial, and social capital. The aims of the research were to analyze the impacts of temporary suspension of one of rubber operational factory to the rubber tapper households, to find out the conditions of rubber tapper household assets, and to analyze the livelihood strategy that being used by the rubber tapper households in order to fulfill their family living. This research conducted in March 2020 at PT Perkebunan Nusantara IX Kebun Batujamus, Kuto Village, Kerjo Sub-district, Karanganyar Regency. The data of the research collected by using methods such as observation, documentation, indepth interview, and literature study. The informants of the research consisted of 12 key informants and 3 supporting key informants. The data of the research was analyzed using descriptive qualitative method and analysis method of Miles and Huberman interactive data model. The research also used source and methodological triangulation. The research results showed that the temporary suspension of one of the company’s factories had an impact to the rubber tapper promotion. Rubber tapper households used multiple livelihood strategy, which was combining the on-farm income and off-farm income.